1989
DOI: 10.1104/pp.90.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Whole Plant and Leaf Steady State Gas Exchange during Ethylene Exposure in Xanthium strumarium L.

Abstract: The effects of ethylene evolved from ethephon on leaf and whole plant photosynthesis in Xanthium strumarium L. were examined. Ethylene-induced epinasty reduced light interception by the leaves of ethephon treated plants by up to 60%. Gas exchange values of individual, attached leaves under identical assay conditions were not inhibited even after 36 hours of ethylene exposure, although treated leaves required a longer induction period to achieve steady state photosynthesis. The speed of translocation of recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…These data support the hypothesis that C2H4 exerts its effects on gas exchange directly. Although Glycine max does respond to exogenous C2H4 with epinastic changes in leaf angle, the hypothesis (17) that these changes in leaf angle account entirely for the reductions in PN is not supported by these studies. In fact, the magnitude of the reduction in gas exchange reported here is comparable to that reported previously for G. max in nonsteady-state single leaf cuvette studies (PN reduced to 69-75% of control, g, reduced to 32-52% of control; 3, 1 1,12).…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…These data support the hypothesis that C2H4 exerts its effects on gas exchange directly. Although Glycine max does respond to exogenous C2H4 with epinastic changes in leaf angle, the hypothesis (17) that these changes in leaf angle account entirely for the reductions in PN is not supported by these studies. In fact, the magnitude of the reduction in gas exchange reported here is comparable to that reported previously for G. max in nonsteady-state single leaf cuvette studies (PN reduced to 69-75% of control, g, reduced to 32-52% of control; 3, 1 1,12).…”
Section: Discussionmentioning
confidence: 68%
“…They further suggest (16)(17)(18) that reports of direct effects on gas exchange such as we have reported in soybean (3,11,12) have been biased by nonsteady-state conditions and leaf angle changes. They have concluded that reduced light interception and lower photosynthetic induction states of epinastic leaves account for any reported reductions in gas exchange in response to C2H4.…”
mentioning
confidence: 57%
See 3 more Smart Citations